Uji Potensi Antijerawat Secara In Vitro dan Ex Vivo dari Ekstrak Etanol Herba Alfalfa (Medicago sativa L.) - Erika Indah Safitri; Risha Fillah Fithria; Eko Wahyu Saputro; Danang Yogo Wijaya (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Propionibacterium acnes is one of the bacteria that causes acne. Acne problems can be controlled with herbal plants, namely alfalfa herbs. The content of flavonoids in alfalfa herb is efficacious as an antiacne. This study aimed to determine the total flavonoid content and to test the potency of alfalfa herb ethanol extract (AHEE) as an antiacne in vitro and ex vivo induced by Propionibacterium acnes. Determination of total flavonoid levels using the spectrophotometer method with quercetin comparison. Test of alfalfa herbs ethanol extract by in vitro using disk diffusion method in concentration series 40%, 50%, 60%, 70%, and 80%. Meanwhile, test of extract by ex vivo using rabbits induced Propionibacterium acnes bacteria intradermally in 3 optimal concentration from in vitro test (50%, 60%, dan 70%). The parameter of test in the form of zone inhibition and percentage reduction in erythema diameter. Ethanol extract of alfalfa herbs contains total flavonoids of 2,323 mgQE/g. All ethanol extract of alfalfa herbs test concentrations had antibacterial activity against P. acnes with an average diameter of the respective iradic inhibitory area 14,60 mm; 14,89 mm; 15,56 mm; 16,52 mm; and 18,59 mm. The average percentage reduction in erythema diameter by ex vivo on ethanol extract of alfalfa herbs (50%, 60%, and 70%) were 48.70%, 48.26%, and 54.09%, respectively.